Effect of Prepackaged Polymer on Compressive, Tensile and Flexural Strength of Mortar - Memon, N. A.; Larik, A. H.; Bhutto, M. A.; Lakho, N. A.; Memon, M. A.; Memon, A. N. (Engineering, Technology & Applied Science Research, 2018)
Synthetic materials, like various types of polymers, are introduced as having cementitious qualities, which improve the system of pores of mortars and concretes by the formations of polymer films and thereby enhancing their strength and durability. This experimental study focuses to use a water-based pre-packaged grout powder containing polymer as cementitious material available in the local market under the brand ‘Hi- bond (universal)’ in mortar. The Hi-bond is added in mortar as partial replacement of cement. The replacement levels were from 2.5% to 10% of cement by weight with an increment of 2.5%. In addition, same proportions mortar without Hi-bond, was also tested to compare the Hi-Bond effectiveness in mortar. Mortars of three proportions; 1:2, 1:3 and 1:4 were cast and tested. The water-binder ratio was fixed at 0.5. The specimens were cured in three curing conditions i.e., water, room temperature and natural environment (outside the room, open to sky). All specimens were tested after 28 days of curing. The mortar performance with and without Hi-Bond was investigated in terms of compressive strength, tensile strength and flexural strength. Enhancements in almost all the strength properties of mortar with Hi-bond were observed. A pronounced effect of curing condition and the mortar proportion is observed on the strength properties of the prepackaged polymer.